2019
DOI: 10.1002/pits.22318
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent academic achievement: A model of social support and grit

Abstract: Grit has been defined as passionate perseverance toward long‐term challenging goals and it is associated with various positive outcomes for youth, including academic achievement. However, less is known about these associations for the two facets of grit (i.e., perseverance of effort, consistency of interest) and few studies have examined the link between grit and perceived social support. The present study examined the group‐level demographic differences (i.e., gender, grade, socioeconomic status, and special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 37 publications
3
24
0
1
Order By: Relevance
“…Moreover, according to the socioecological framework (Bronfenbrenner, 2001), a favorable social context may magnify the buffering effect of individual characteristics (e.g., grit) on depressive symptoms in young adults. For example, Clark et al (2020) found that the positive association between grit and academic achievement is stronger for high school students reporting high social support from teachers, explaining that when students perceive greater social support, they are more likely to study toward long-term goals with passion and achieve higher grades. Although this empirical finding gives us some possible indications, it is still unclear how those variables may contribute in interactive ways to the association between COVID-19 infection risk and depressive symptoms, as a study of high school students and academic achievement differs substantially from the context of young adults and their emotional reactions to quarantine.…”
Section: Gritmentioning
confidence: 99%
“…Moreover, according to the socioecological framework (Bronfenbrenner, 2001), a favorable social context may magnify the buffering effect of individual characteristics (e.g., grit) on depressive symptoms in young adults. For example, Clark et al (2020) found that the positive association between grit and academic achievement is stronger for high school students reporting high social support from teachers, explaining that when students perceive greater social support, they are more likely to study toward long-term goals with passion and achieve higher grades. Although this empirical finding gives us some possible indications, it is still unclear how those variables may contribute in interactive ways to the association between COVID-19 infection risk and depressive symptoms, as a study of high school students and academic achievement differs substantially from the context of young adults and their emotional reactions to quarantine.…”
Section: Gritmentioning
confidence: 99%
“…More recently, Clark et al (2020) adopted 36 survey items from the 60-item CASSS instrument (Kerres & Kilpatrick, 2002) for their investigation of the role of social support and grit on adolescents' academic achievement.…”
Section: Social Support Scale and Its Impact On Educational Outcomesmentioning
confidence: 99%
“…The shortened version of 36-item multidimensional social support measure had good reliability scores, alphas = 0.95, 0.96, and 0.96, respectively. However, Clark et al (2020) did not examine measurement of invariance as the participants of their study were limited to a single homogeneous adolescent group.…”
Section: Social Support Scale and Its Impact On Educational Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in this study, the role of academic and psychological variables in the academic success of the national level exam has been discussed. Other factors related to academic performance, such as socioeconomic status (e.g., Saenz et al, 1999), personality traits (e.g., Wolfe & Johnson, 1995), cognitive ability (Harackiewicz et al, 2002b), grit (Clark et al, 2020), social focus in school (Jones & Mueller, 2017) and learning strategies (Loranger, 1994; Özkal & Çetingöz, 2006; Phakiti, 2003) were not included in this study. Further research with these variables may contribute to our knowledge of the national achievement test success.…”
Section: Limitations and Suggestionsmentioning
confidence: 99%